Connected dominating set for wireless ad hoc networks: a survey. (4th December 2014) - Yadav, Anil Kumar; Yadav, Rama Shankar; Singh, Raghuraj; Singh, Ashutosh Kumar
In wireless ad hoc networks, there is no predefined infrastructure and nodes can communicate with each other via relaying the messages through intermediate nodes. The ad hoc network has found a variety of military and civil applications such as battlefield communication, disaster recoveries, conferences, environmental detection, security, pollution sensing and traffic monitoring. Connected dominating sets (CDS) can be regarded as a virtual backbone for wireless ad hoc network and a smaller CDS is designed to minimise the interference problem, control messages and maintenance cost. The objective of designing a CDS heuristic is to reduce the search space to save scarce resources such as bandwidth energy. We discuss few centralised algorithms that have constant performance ratios for its size. We also discuss few algorithms of distributed and localised type. Further, we compare various CDS algorithms in terms of performance ratio, time complexity, message complexity with their merits and demerits and are illustrated in Table